1991
DOI: 10.1103/physrevlett.67.3106
|View full text |Cite
|
Sign up to set email alerts
|

Removing multiple scattering and twin images from holographic images

Abstract: Properly phased combinations of images reconstructed from holograms recorded at several wavenumbers suppress inter-object multiple scattering, self-interference, and the troublesome holographic twin image. When applied to point-source electron holographies, this solves the longstanding problem of electron multiple scattering confusing the determination of surface structure; when applied to in-line holograms of any kind it solves the classical problem of twin images which dates from the original work of D. Gabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
250
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(251 citation statements)
references
References 17 publications
1
250
0
Order By: Relevance
“…show the experimental and calculated images, respectively. The Barton algorithm 23) was used for the reconstruction. Figure 3(c) shows the atomic con gurations in a Zn plane located on the stacking fault based on the model proposed by Egusa and Abe 15) .…”
Section: Resultsmentioning
confidence: 99%
“…show the experimental and calculated images, respectively. The Barton algorithm 23) was used for the reconstruction. Figure 3(c) shows the atomic con gurations in a Zn plane located on the stacking fault based on the model proposed by Egusa and Abe 15) .…”
Section: Resultsmentioning
confidence: 99%
“…Barton's algorithm for multiple energy reconstruction was applied to the processed data. 17) The (001), (004), (110) and (100) planes were reconstructed for all samples. All observed atomic images elongate along the c-axis due to the limited k z range of the measured holograms.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned previously, in Auger emission applications, the electron source is within atomic distances of the object, while in LEEPS microscopy the electron source is at a large distance from the atomic cluster. It has also been shown that multiple scattering does tend to obscure images in some LEED applications, and that improvements can be made in reconstructing the holograms [21,22]. Images in some LEED applications are also obscured by``twin'' images, which are virtually not present in LEEPS images due to the large distances from source to object.…”
Section: Multiple Scattering In Leed Vs Leepsmentioning
confidence: 99%
“…Images in some LEED applications are also obscured by``twin'' images, which are virtually not present in LEEPS images due to the large distances from source to object. It was shown that by energy averaging [21], and averaging over the angle of collection [22] the e ects of multiple scattering on reconstructed images could be signi®cantly reduced. That is, the quality of the images were improved by averaging holograms of di erent energies and screen positions, respectively.…”
Section: Multiple Scattering In Leed Vs Leepsmentioning
confidence: 99%